Research on Calculation Method of “Gantry” Anti-floating Structure Underneath a River Channel in Shenzhen Metro Line 9 - LU Bin; WANG Guojian (Renmin Zhujiang)
A river channel in Shenzhen intersects with the tunnel of Metro Line 9 vertically,with the overburden thickness of 1.87 m only,and “gantry” pile raft structure to assist anti-floating.This paper simplifies the force model of the “gantry” anti-floating pile raft structure,analyzes the internal force and displacement of the structure with the structural mechanics method,and verifies and rechecks them by the finite element method.The results show that the bending moment of “gantry” pile raft obtained by the structural mechanics is similar to that calculated by the finite element method,and the shear force and displacement are larger than those calculated by the finite element method.The “gantry” anti-floating pile raft structure is widely used.In addition,the calculation method in this paper can provide a reference for similar projects.